Pengaruh Aromaterapi Mawar terhadap Tingkat Kecemasan Pasien Pre Operasi dengan Spinal Anestesi di RS PKU Muhammadiyah Gamping - Heni Agustini; Joko Murdiyanto; Nia Handayani (Inovasi Kesehatan Global, 2025)
Preoperative anxiety is common for patients, especially those who will undergo spinal anesthesia. The level of anxiety can vary, from mild anxiety to panic attacks, which can potentially affect the outcome of surgery and the recovery process. To overcome this problem, rose aromatherapy with a diffuser offers a non-pharmacological solution. A study was conducted in the Operating Room of PKU Muhammadiyah Gamping Hospital to determine the effect of rose aromatherapy on the level of anxiety of pre-operative patients with spinal anesthesia. This study used a pre-experimental one group pretest posttest design, which showed that rose aromatherapy can significantly reduce anxiety levels in patients who will undergo surgery with spinal anesthesia. This study involved 30 respondents selected through a purposive sampling technique. Data were collected using a questionnaire and analyzed statistically using the Wilcoxon Signed Rank Test. The results of the analysis showed a significance value of 0.000, which means that there is a significant effect of giving rose aromatherapy on the level of patient anxiety. In other words, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Conclusion, rose aromatherapy is proven to be effective in reducing pre-operative anxiety in patients with spinal anesthesia at PKU Muhammadiyah Gamping Hospital. This study is expected to be an additional reference for future research and provide valuable information for health workers in pre-operative anxiety intervention efforts.